Presumed topiramate retinopathy: a case report. (December 2016) - Yeung, Tiffany; Li, Patrick; Li, Kenneth
Abstract Background We report a case of peripheral pigmentary retinopathy and visual field loss following topiramate use for uncontrolled seizures. Such side effects have not been well documented despite the increasing use of topiramate in the past 10 years. A thorough search of available English literature revealed only a small number of reports of topiramate-induced retinopathy or visual field defects in humans. One similar case has been described. We are concerned about the possible rare instances of this occurrence in future patients and hence would like to propose a presumed correlation. Case presentation A 48-year-old Chinese woman developed blurred vision after 9 months of topiramate use. Her visual acuity dropped from 1.2 to 0.7 in both eyes, with bilateral diffuse pigmentary retinopathy and a constricted visual field. Despite an improvement in visual acuity after cessation of the drug, the other clinical findings remained. The temporal relationship between the initiation of topiramate and the visual disturbance suggests that topiramate could be the cause of such signs and symptoms. Conclusion Topiramate potentially causes pigmentary retinopathy and constricted visual field.